The role of iron in neurodegenerative disorders: insights and opportunities with synchrotron light - Collingwood, Joanna F.; Davidson, Mark R. (Frontiers in Pharmacology, 2014)
There is evidence for iron dysregulation in many forms of disease, including a broad spectrum of neurodegenerative disorders. In order to advance our understanding of the pathophysiological role of iron, it is helpful to be able to determine in detail the distribution of iron as it relates to metabolites, proteins, cells, and tissues, the chemical state and local environment of iron, and its relationship with other metal elements. Synchrotron light sources, providing primarily X-ray beams accompanied by access to longer wavelengths such as infra-red, are an outstanding tool for multi-modal non-destructive analysis of iron in these systems. The micro- and nano-focused X-ray beams that are generated at synchrotron facilities enable measurement of iron and other transition metal elements to be performed with outstanding analytic sensitivity and specificity. Recent developments have increased the scope for methods such as X-ray fluorescence mapping to be used quantitatively rather than semi-quantitatively. Burgeoning interest, coupled with technical advances and beamline development at synchrotron facilities, has led to substantial improvements in resources and methodologies in the field over the past decade. In this paper we will consider how the field has evolved with regard to the study of iron in proteins, cells, and brain tissue, and identify challenges in sample preparation and analysis. Selected examples will be used to illustrate the contribution, and future potential, of synchrotron X-ray analysis for the characterization of iron in model systems exhibiting iron dysregulation, and for human cases of neurodegenerative disorders including Alzheimer’s disease, Parkinson’s disease, Friedreich’s ataxia and Amyotrophic Lateral Sclerosis.